A study of burnout and stressor related factors among nurses caring for children in Hospital Sains Malaysia - Hussain, Siti Fatimah Abu (2020)
Objective: The aim of the study is to determine the prevalence of burnout and correlation between burnout score and stressor domain score and to determine the association between sociodemographic and occupational related factors with overall burnout among nurses caring for children in Hospital Universiti Sains Malaysia (Hospital USM). Materials and Methods: This was a cross-sectional study using bilingual validated questionnaire; the General Stressor Questionnaire (GSQ) and Copenhagen Burnout Inventory (CBI) conducted among nurses providing medical service for children in Hospital USM particularly in wards and clinic. All 159 eligible nurses were recruited and 157 completed questionnaires were analysed. Descriptive statistics were examined for all variables under study. Pearson’s correlation analysis was applied to study the correlation while simple logistic regression and multiple logistic regressions were applied to study the association. Results: The prevalence of burnout among nurses caring for children in Hospital USM was 28.7% (95% CI = 21.6, 35.7) with the majority of them experienced personal burnout (49.7%, 95% CI = 41.9, 57.5). There was a significant moderate positive correlation between different stressor domain score with an overall burnout score with p-value < 0.05. Work placement and bureaucratic constraints were identified as the main contributory factor leading to overall burnout. Conclusion: Burnout among nurses providing medical services for children in Hospital USM is of concern especially involving personal burnout. The main stressor related factors of burnout were work placement and bureaucratic constraints. Therefore, burnout among nurses providing care for children must be addressed in order to enhance their psychological wellbeing.